A Humanistic Education Approach and Restorative Justice To Increase Juvenile Legal Compliance - Himawan, Agung (International Journal of Research in Counseling, 2023)
Wonocolo Polrestabes Surabaya Police Station has taken effective steps and approaches in dealing with juvenile brawl delinquency in their area. They use a humanistic education approach that focuses on the protection of human rights and a restorative justice approach. In handling these cases, Wonocolo Police conducted literature studies, interviews, documentation, and observation as data collection methods. The data were then analysed using the instruments of humanistic education approach and restorative justice. The results showed that the efforts made by Wonocolo Police have succeeded in increasing legal compliance among teenagers, by promoting an approach that respects and protects their rights. In dealing with this problem, Wonocolo Police Station has proven that they can be a good example in handling teenage brawls by prioritising an educative approach, using a humanistic approach, and restorative justice to protect children and ensure their healthy growth physically and psychologically.